Perilaku pembersihan gigi tiruan lengkap pada Lansia panti werdha hana - Falatehan, Niko; Andreas, Rama (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Behavior in cleaning full denture in the elderly has an important role in the success of complete denture treatment. This behaviour is an important thing so that patients can maintain the cleanliness of full denture and the health of their oral cavity. This study aims to determine the full denture cleaning behavior in the elderly. Methods: This type of research was descriptive observational with a cross-sectional design conducted on 32 elderly people in Hana Nursing Home, Pamulang, South Tangerang. The behavior of the elderly is measured through a questionnaire that has been provided previously. Results:The results of the descriptive statistical test showed that in general the behavior of cleaning of the elderly at the Hana Nursing Home had good results (46.9%). This good behavior is obtained based on good knowledge (59.4%), fairly good attitude (56.3%), and fairly good actions (53.1%). Based on gender grouping, it was obtained by the elderly group of men having full denture cleaning behavior which entered into a fairly good category (50%). Whereas the elderly woman in the Hannah Nursing Home has cleaning behavior that is included in the good category (50%). Based on age grouping, it can be seen that full denture cleaning behavior is good for the eldery age group (60-74 years), whereas in the old age group (75-90 years) and very old age group (> 90 years) has a cleaning behavior is in fairly good category. Conclusion:The behavior of cleaning the full denture influenced by the knowledge, attitudes and actions taken by the elderly full denture users.